Pola Pembinaan Keagamaan Di SMA Plus Boarding School Astha Hannas Subang - Haris Munandar (UIN Sumatera Utara Medan, 2018)
Religious education is taught in Indonesian school. One of them is in SMA Plus Boarding School Astha Hannas. The problems raised from this research are (1) what is boarding school? (2) what religious values do you want to achieve in SMA Plus boarding school Astha Hannas? (3) How is the strategy used by the high school in instilling religious values in the students? (4) how is the result of the implementation of coaching students in SMA Plus Boarding School Astha Hannas ?. The data collection techniques used interviews, observation and documentation. After the field data got obtained then analyzed and discussed so as to produce factual explanation about Religious Boarding School Development Model.